Human agency in disaster risk reduction: theoretical foundations and empirical evidence from people with disabilities. (20th October 2021) - Ton, Khanh That; Gaillard, J. C.; Adamson, Carole Elizabeth; Akgungor, Caglar; Ho, Ha Thanh
ABSTRACT: To date, the agency of people with disabilities has seldom been elaborated theoretically and empirically in disaster research. Drawing on the capability approach, this paper examines the agency of people with disabilities to deal with disasters. Their agency is explored in relation to their participation in decision-making processes which has long regarded as a means to disaster risk reduction. A case study design with the use of focus group discussions and interviews was adopted in this study. A rural commune in Vietnam was selected as a case study context. The study found that, in most cases, people with disabilities need to participate in decision-making processes in order to achieve their valuable capabilities for their safety in times of disaster. This process of participation can be seen as both an end and a means. As an end, it refers to involvement in decision-making processes. As a means, it is viewed as a process in which people with disabilities individually or collectively exert their agency (i.e. raising their voice, influencing the decision-making and transforming the decisions into actions). For participation as a means to be achieved, however, participation as an end must be secured.